Community-led management maintains higher predator biomass supporting kelp forests persistence in Baja California - Jeremie Bauer; Rodrigo Beas-Luna; Luis Malpica-Cruz; Alicia Abadía-Cardoso; Paulina Filz; Juan Carlos Bonilla; Julio Lorda (Scientific Reports)
Abstract Community-led management in small-scale fisheries represents an alternative approach to marine ecosystem conservation. This work examines the effectiveness of community-led marine reserves (MRs) by comparing kelp forest canopy coverage and predator populations between two regions with different social-ecological conditions along the Pacific coast of Baja California, Mexico. We analyzed kelp canopy coverage from 2004 to 2023, spanning periods before, during, and after extreme marine heatwaves (2014–2016). Additionally, we compared the density, size, and biomass of three key predator species (spiny lobster, California sheephead, and horn shark) between community-led MRs and federally managed marine protected areas (MPAs). Our analyses revealed significant regional differences in kelp forest coverage recovery following extreme warming events, with the southern region maintaining historical coverage levels while the northern region showed a 95% decline in 2023. Community-led MRs maintained significantly higher densities and biomass of predator species compared to federally managed areas, with spiny lobsters and horn sharks completely absent from northern MPAs and California sheephead showing larger sizes in community-led MRs. These findings demonstrate that community-led MRs maintain predator populations, which may be crucial for future management scenarios given the importance of predator–prey relationships in kelp forest ecosystems. For policymakers, our results suggest that incorporating local governance and community-based approaches into marine management frameworks, particularly in regions with strong fishing cooperatives and traditional management practices, could enhance conservation outcomes. This study provides evidence from the Global South that locally managed, participatory approaches can achieve effective conservation outcomes, offering insights for regions facing similar challenges in balancing resource use with ecosystem protection.